2013
DOI: 10.1248/bpb.b13-00235
|View full text |Cite
|
Sign up to set email alerts
|

Sesamin Induces Cell Cycle Arrest and Apoptosis through the Inhibition of Signal Transducer and Activator of Transcription 3 Signalling in Human Hepatocellular Carcinoma Cell Line HepG2

Abstract: Sesamin, one of the most abundant lignans in sesame seeds, has been shown to exhibit various pharmacological effects. The aim of this study was to elucidate whether sesamin promotes cell cycle arrest and induces apoptosis in HepG2 cells and further to explore the underlying molecular mechanisms. Here, we found that sesamin inhibited HepG2 cell growth by inducing G2/M phase arrest and apoptosis. Furthermore, sesamin suppressed the constitutive and interleukin (IL)-6-induced signal transducer and activator of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 31 publications
(41 reference statements)
1
33
0
Order By: Relevance
“…Sesamin of 25–125  μ M could induce HepG2 cell death involving apoptosis [36]. Content of sesamin in free phenolic extract of B2 variety was nearly 39.55 mg kg −1  DW, which is roughly equivalent to 11  μ M sesamin.…”
Section: Resultsmentioning
confidence: 99%
“…Sesamin of 25–125  μ M could induce HepG2 cell death involving apoptosis [36]. Content of sesamin in free phenolic extract of B2 variety was nearly 39.55 mg kg −1  DW, which is roughly equivalent to 11  μ M sesamin.…”
Section: Resultsmentioning
confidence: 99%
“…The lignan (10–100 μM) also inhibited the pro-angiogenic activity of macrophages in MCF-7 cells by down-regulating VEGF and MMP-9 [162]. Besides, it was suggested that STAT3 played an important role in sesamin (25–125 μM) induced G 2 /M cell cycle arrest and apoptosis in HepG2 cells [163]. Sesamin (10–100 μg/mL) could suppress lipopolysaccharide-induced proliferation and invasion of PC3 prostate cancer cells by modulating the p38-MAPK and NF-κB signaling pathways.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Sesamin (SES) is one of the most abundant ligand in sesame seeds (Phitak et al, 2012). It has been shown to exhibit multiple biological functions, such as inhibition of inflammation (Lin et al, 2014), carcinogenesis (Deng et al, 2013) and oxidative stress (Hsieh et al, 2011). In addition, sesamin has been reported to attenuate hypertension (Matsumura et al, 1995), serum and hepatic cholesterol (Hirata et al, 1996), serum triglycerides (Fukuda et al, 1998), cerebral thrombogenesis (Noguchi et al, 2004), and neuroinflammation (Bournival et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%